Chokeberry juice affects membrane lipid status and cellular antioxidant enzymes in healthy women with aerobic training activity - Nevena Vidović; Ana Pantović; Vuk Stevanović; Ivana Šarac; Kristina Robal; Stevan Stevanović; Maria Glibetic (University of Novi Sad, Faculty of Sport and Physical Education, 2022)
The present study examined the effects of aerobic training alone or combined with chokeberry juice on membrane lipid status and activities of antioxidant enzymes in non-athlete women. Participants were randomly assigned into the training group performing aerobic training three times per week; the chokeberry-training group followed the same training regime and additionally consumed 100 ml of chokeberry juice per day and the control group neither trained nor consumed the juice. Blood samples were collected at baseline and the end of the eight-week-long intervention. Membrane fatty acids' composition was analyzed by gas-liquid chromatography, while the activities of antioxidant enzymes were measured by spectrophotometry. As a result, the n-3 fatty acids' content was significantly higher in the chokeberry-training (median (interquartile range) of 5.96 (1.65) %) compared with the control group (5.12 (0.87) %), while saturated fatty acids' content was lower in the chokeberry-training (40.14±1.19 %) than in the training group (42.59±2.29 %). We detected significantly higher activity of superoxide dismutase in the training (2224 (2170) U/gHb) compared with the chokeberry-training (1252 (734) U/gHb) and control group (1397 (475) U/gHb). Our study indicates that supplementation with chokeberry juice may induce favorable changes in cell fatty acid composition and antioxidant response in women performing aerobic training.